ABOUT PROBLEMS OF DEVELOPMENT OF ALGORITHMIC THINKING OF UNIVERSITY STUDENTS IN RELATION TO CREATION OF APPLICATIONS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This article presents the problems of developing students' algorithmic thinking in programming and suggestions and recommendations for their solution.